Analisis Laporan Keuangan untuk Menilai Kinerja Keuangan pada Koperasi Pegawai Republik Indonesia Kopin Pengayoman Lapas Kabupaten Garut - Tinneke Hermina (Jurnal Wacana Ekonomi, 2016)
This study aims to determine the financial performance of cooperatives. The object of this research is the Employee Cooperative of the Republic of Indonesia, KOPIN Pengayoman Lapas, Garut Regency in 2014-2016. The analytical method used is the ratio of liquidity, solvency, and profitability using Microsoft Excel 2016. The data from this study were obtained from the results of company documents in the form of financial statements of the Republic of Indonesia Employee Cooperative, KOPIN Pengayoman Lapas, Garut Regency in 2014-2016. The results of this study indicate that the liquidity ratio is measured using Current Ratio, 2014-2016 shows that financial performance is classified as very healthy and Cash Ratio, in 2014-2016 shows that financial performance is classified as a fairly healthy condition. The solvency ratio measured using the Debt to Equity Ratio 2014 to 2016 shows that financial performance is classified as healthy and the Debt to Assets Ratio in 2014 to 2016 shows that financial performance is classified as unhealthy. Profitability ratios measured using Economic Rentability, 2014 to 2015 indicate that financial performance is classified as unhealthy and Own Capital Rentability during 2014 to 2016 shows that financial performance is classified as unhealthy.